2020
DOI: 10.18632/aging.103316
|View full text |Cite
|
Sign up to set email alerts
|

Integrative analysis of miRNAs-mRNAs reveals that miR-182 up-regulation contributes to proliferation and invasion of nasopharyngeal carcinoma by targeting PTEN

Abstract: Objective: Several miRNAs have been found to be abnormally expressed during nasopharyngeal carcinoma development. Nevertheless, the interaction between miRNAs and downstream genes remains unexploited. In this study, we aim to investigate miRNAs-mRNAs interaction and the mechanism of miR-182 in NPC. Results: Integrative analysis identified several hub-miRNAs that drive NPC pathogenesis. The expression of miR-182 was notably increased in 32 NPC tissues and cell lines (CNE1 and 5-8F). Up-regulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
(32 reference statements)
3
3
0
Order By: Relevance
“…The dual-luciferase reporter gene assay confirmed that miR-107 decreased the transcription of TPM3-WT, while the fluorescence intensity did not change significantly in the plasmid containing TPM3-MUT. This confirmed the predicted binding area in 3'UTR (Figure 5B), which is a classical kind of regulating pattern between miRNAs and mRNAs (27,28). Furthermore, the experiments revealed that miR-107 mimics limited the proliferation, invasion, and migration, but facilitated the apoptosis of ESCC cell lines.…”
Section: Mir-107 Plays An Anti-cancer Role In Escc By Inhibiting Tpm3...supporting
confidence: 81%
“…The dual-luciferase reporter gene assay confirmed that miR-107 decreased the transcription of TPM3-WT, while the fluorescence intensity did not change significantly in the plasmid containing TPM3-MUT. This confirmed the predicted binding area in 3'UTR (Figure 5B), which is a classical kind of regulating pattern between miRNAs and mRNAs (27,28). Furthermore, the experiments revealed that miR-107 mimics limited the proliferation, invasion, and migration, but facilitated the apoptosis of ESCC cell lines.…”
Section: Mir-107 Plays An Anti-cancer Role In Escc By Inhibiting Tpm3...supporting
confidence: 81%
“…However, luciferase assay results showed that miR‐182 did not target Mob1 (Figure 4I), suggesting that it may regulate activation of the HIPPO pathway in other ways. PTEN has been found to be a direct target of miR‐182 35 . At the same time, this study also found that miR‐182 and PTEN expression showed a significant negative correlation (Figure 4H).…”
Section: Discussionsupporting
confidence: 68%
“…PTEN has been found to be a direct target of miR-182. 35 At the same time, this study also found that miR-182 and PTEN expression showed a significant negative correlation (Figure 4H). Therefore, we hypothesized that miR-182 may indirectly regulate the activation of HIPPO pathway by targeting PTEN/AKT pathway.…”
Section: Discussionsupporting
confidence: 60%
“…In breast cancer, it was shown that the expression of miR-182-3p was significantly increased compared to a healthy individual; the increased onco-microRNA-182-3p inhibited T cells [ 10 ]. Additionally, Shi et al (2020) [ 12 ] demonstrated that the proliferation and invasion of nasopharyngeal cancer cells were significantly increased in cells with miR-182-3p overexpression. However, in osteosarcoma (OS), the low expression of miR-182-3p in OS cell lines compared to hMSC was observed.…”
Section: Discussionmentioning
confidence: 99%